How does marine technology diffuse across cities? Evidence from China - Mao, Xuankai; Cui, Wanglai; Zhong, Haiyue; Yang, Yang; Zhu, Yiqing (Frontiers in Marine Science, 2025)
Marine science and technology have become a new battleground for global marine competition, and the extent of urban marine technology diffusion determines the quality and speed of marine scientific and technological innovation. This study uses marine patents as an entry point, establishes a marine technology classification system, and characterizes marine technology diffusion through the transfer of marine technology patents. By analyzing the spatio-temporal evolution of marine technology diffusion in Chinese cities from 2001 to 2023, it identifies technological hotspots, core participants, and classifies types of urban transformation in marine technology diffusion activities. It also explores the driving mechanisms of inter-city marine technology diffusion. The study finds that: ① from the perspective of temporal evolution, marine biomedical technology and marine high-end equipment technology continue to lead marine technology diffusion in China’s technology trading market, with enterprises maintaining their dominant position. Cross-city flow of marine technology has become the norm, and the role of cities has gradually shifted from self-sufficient intra-city flow to open and innovative inter-city exchange. ② Spatially, marine technology diffusion activities reveal an intra-city “Π”-shaped pattern formed by the Coastal Economic Belt, Yangtze River Economic Belt, and Longhai-Lanxin Economic Belt. Inter-city marine technology diffusion has formed a diamond-shaped network with Beijing-Tianjin, the Yangtze River Delta, Pearl River Delta, and Sichuan-Chongqing region as hubs. ③ Regarding driving mechanisms, exogenous and endogenous forces shape China’s inter-city marine technology diffusion network. Network self-organization, merit-based linkages, and intermediary effects promote the development of the diffusion network. Under multi-dimensional proximity, China’s inter-city marine technology diffusion exhibits complementary synergies and symbiotic development characteristics, forming a strong network correlation mechanism.